Témoignage d’un lecteur de la revue depuis 1977 - Thierry Courtin (Recherches Germaniques)
As an avid reader of the academic journal Recherches germaniques since 1977, I would like, on its fiftieth anniversary, to look back at the context surrounding my discovery of the Journal through its issue n.7. My contribution will then underline the originality of the themes addressed in the Varia and the Special Issues and show how they have enriched my life during all these years, both from personally and professionally standpoint. I have therefore chosen a few major themes, ranging from medieval studies to poetry, art, philosophy, etc. and highlight their erudition, relevance and interest for a Germanist or a Germanophile of today.